2020
DOI: 10.1177/2150132720946951
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the COVID-19 Nutrition Crisis in Vulnerable Communities: Applying a Primary Care Perspective

Abstract: The coronavirus disease (COVID-19) pandemic and subsequent public health interventions have disrupted food systems all over the world. In the Philippines, where stringent lockdown rules have been implemented, households living in poverty have had to rely largely on food aid in the form of food packs distributed by local governments and private donors. An evaluation of the commonly distributed food items reveals a diet that addresses acute hunger but does not contain sufficient nutrients to promote and maintain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 3 publications
0
15
0
3
Order By: Relevance
“…Kalu et al, 2020 [30] Addressing the COVID- Ong et al, 2020 [31] Quadro 1 (continuação) Toffolutti et al, 2020 [32] Food System Workers are the Unexpected but Under Protected COVID Heroes.…”
Section: Austráliamentioning
confidence: 99%
See 2 more Smart Citations
“…Kalu et al, 2020 [30] Addressing the COVID- Ong et al, 2020 [31] Quadro 1 (continuação) Toffolutti et al, 2020 [32] Food System Workers are the Unexpected but Under Protected COVID Heroes.…”
Section: Austráliamentioning
confidence: 99%
“…O artigo de Ong et al . [31] apresenta que nas Filipinas o Departamento de Bem-Estar Social e Desenvolvimento identificou, desde então, cerca de 21 milhões de famílias de baixa renda que precisam urgentemente de ajuda monetária e alimentar do governo durante esta pandemia. Além disso, regras rígidas de isolamento social foram implementadas e famílias que vivem na pobreza tiveram que contar em grande parte com ajuda de alimentos processados e ultraprocessados, distribuídos por governos locais e doadores privados.…”
Section: Contexto Mundial Em Alguns Paísesunclassified
See 1 more Smart Citation
“…Inadequate diets are known to be associated with poverty (157)(158)(159)(160)(161)(162). This is especially pronounced during the COVID-19 pandemic (163). Moreover, such diets are often deficient in protein containing the amino acid tryptophan, which can lead to low MT as tryptophan is the essential starting molecule for MT synthesis (41,42,44,164,165).…”
Section: Susceptibility Dietmentioning
confidence: 99%
“…Studies have shown that these measures can lead to dietary changes during the lock-up period, leading to malnutrition or obesity. 3,4 It can also have negative effects on mental health, such as sleep problems, depression, anxiety, and fear of death. 5 In this unprecedented situation, the relationship between men and women, individual sexual behavior, and family function had also undergone unique changes among adults aged 18-44 years.…”
Section: Introductionmentioning
confidence: 99%